EVALUATION OF THE E-LEARNING SYSTEM OF PT. OTAK KANAN THROUGH BLACKBOX TESTING AND SYSTEM USABILITY SCALE (SUS) - Herdianto, Liga Bayu (Universitas Lampung, 2023)
In everyday life and education, the internet and information systems play a key role in providing information services to the educational community. Learning has transformed into an online method known as e-learning, which utilizes technology as a means of education. PT. Otak Kanan is currently introducing E-Learning to support students and interns, and they are developing the E-learning Sigarda application. Software testing is an essential part of this process to ensure the quality and functionality of the application and to prevent errors during development. In the testing of the E-Learning Sigarda application, the Blackbox Testing method is used to examine the application's functionality, while the System Usability Scale method is employed to measure user satisfaction. The test results demonstrate the application's alignment with test case scenarios on both admin and user pages. Additionally, the system's E-Learning testing, using the System Usability Scale method with 15 respondents, yielded a score of 91, falling within the